Simplify. 3−(4x−5)+6 (1 point) Responses −4x+14negative 4 x plus 14 4x+44 x plus 4 12x+2112 x plus 21 −4x+4

1 answer

To simplify 3 - (4x - 5) + 6, you first need to apply the distributive property to the expression inside the parentheses:

3 - (4x - 5) + 6
= 3 - 4x + 5 + 6

Next, combine like terms:

= -4x + 14

So, the simplified expression is -4x + 14.
Similar Questions
  1. Simplify Algebraic Expressions Quick Check1 of 51 of 5 Items Question Simplify 4x + 8x using the properties of operations.(1
    1. answers icon 1 answer
  2. Simplify Algebraic Expressions Quick Check3 of 53 of 5 Items Question Simplify 2a − 4b +7 + 8a + 6b − 2.(1 point) Responses
    1. answers icon 1 answer
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
more similar questions